Uterus Didelphys in Nulliparous and Multiparous Women - Sinha, Pooja; Hiremath, Ravishekar N.; Ankita; Ghodke , Sandhya (Research Highlights in Disease and Health Research Vol. 6, 2023)
Uterus didelphys is a rare congenital uterine abnormality characterized by the failure of embryogenetic fusion of the Mullerian ducts. It will result in the formation of a double uterus with two distinct cervices, as well as a double vagina with a longitudinal septum. Here, we present two unique uterine didelphys instances with distinctive appearances. A nulliparous woman with post-coital bleeding is the first case. A longitudinal full vaginal septum and two cervical holes were discovered on examination; conservative therapy was used. The USG confirmed the didelphys uterine findings. The patient was counseled and released. The second case involves a multiparous woman who had a previous caesarean delivery, ruptured membranes, and meconium in this term pregnancy and was scheduled for an emergency caesarean section. Intraoperatively, dense adhesions and a mass on the right side of the uterus were discovered, which was later confirmed to be a patent right horn of the uterus. Following a post-caesarean speculum and vaginal examination, uterus didelphys was diagnosed.